Outstanding teachers and ICT - Protopsaltis, Aristidis; Goodwyn, Andrew; Fuller, Carol L. (SIGDOC'09 - Proceedings of the 27th ACM International Conference on Design of Communication, 2009)
This paper presents evidence about expertise in teaching and the use of ICT (Information Communication Technology) to communicate information. Fifty four (54) expert teachers and teaching assistants from infant, primary and secondary schools participated in the study. Participants were nominated by their peers as 'outstanding' in their practice. Semi-structured interviews were conducted, exploring what technology experts have adapted to produce highly effective practice. The current study discusses the results of the demographic data, the technologies expert practitioners use in their teaching and their reasons for using these technologies. © 2009 ACM.
Created from Fastlane, Scopus look-up
Keywords: Expert teaching; ICT; Information processing; Learning; Technology